The Arrival of Zero Trust: What Does It Mean? - Loftus, Michael; Vezina, Andrew; Doten, Rick; Mashatan, Atefeh (Communications of the ACM, 2023)
A conversation about the strategic approach to cybersecurity known as "zero trust" is presented between Michael Loftus, an information technology (IT) consultant, Rick Doten, the vice president (VP) of information security at Centene Corporation and chief internet security officer (CISO) of Carolina Complete Health, Atefeh Mashatan, founder and director of the Cybersecurity Research Lab at Toronto Metropolitan University (TMU), and Andrew Vezina, the CISO at Equitable (EQ) Bank.